3.5q-2.5-2.7q=-0.2q-2.5

Simple and best practice solution for 3.5q-2.5-2.7q=-0.2q-2.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.5q-2.5-2.7q=-0.2q-2.5 equation:


Simplifying
3.5q + -2.5 + -2.7q = -0.2q + -2.5

Reorder the terms:
-2.5 + 3.5q + -2.7q = -0.2q + -2.5

Combine like terms: 3.5q + -2.7q = 0.8q
-2.5 + 0.8q = -0.2q + -2.5

Reorder the terms:
-2.5 + 0.8q = -2.5 + -0.2q

Add '2.5' to each side of the equation.
-2.5 + 2.5 + 0.8q = -2.5 + 2.5 + -0.2q

Combine like terms: -2.5 + 2.5 = 0.0
0.0 + 0.8q = -2.5 + 2.5 + -0.2q
0.8q = -2.5 + 2.5 + -0.2q

Combine like terms: -2.5 + 2.5 = 0.0
0.8q = 0.0 + -0.2q
0.8q = -0.2q

Solving
0.8q = -0.2q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '0.2q' to each side of the equation.
0.8q + 0.2q = -0.2q + 0.2q

Combine like terms: 0.8q + 0.2q = 1q
1q = -0.2q + 0.2q

Combine like terms: -0.2q + 0.2q = 0.0
1q = 0.0

Divide each side by '1'.
q = 0.0

Simplifying
q = 0.0

See similar equations:

| 9x^2-6x+3-2x-11x^2= | | -x+2+10x=-2+5x+32 | | (x-5)(x+1)+5=0 | | 12k^3q^4-4k^2q^5-kq^6=0 | | 7x^2-5-11x^2+10+8x= | | -(5y+1)-(-4y-3)=-2 | | -4x-16=18 | | x+(x+12)+(4x-36)=1056 | | -9x^2+5+10x^2-13x= | | 9p^2-18p+8=0 | | 4x+11=39 | | 15x^2-94x+24=0 | | 7x^4+4=0 | | -9x^2-8+5x+11x^2-13x= | | 8x^4=0 | | -(7y+5)-(-6y-7)=-6 | | t-16=-32 | | 234=10+2x | | 9(4x-4)=3(12x+3) | | 9x^2-5+2x-3x^2-13= | | -7x=27 | | -1.3a=-10.4 | | 234=10x | | 4(3v+3)+v= | | 27t^3-64x^6=0 | | 234=10+x | | x-2=x+24 | | -4u+3+u-4= | | p^3+512=0 | | m^3-8=0 | | s=p-12 | | 11y-17=8y+1 |

Equations solver categories